Radiologic Technique for Esophagus, Stomach, and Duodenum Examination in Dysphagia Cases: A Case Study at Panembahan Senopati Bantul Hospital - Kasman Kelimagun, Dian Fatanah Kelimagun; Istiqomah, Anisa Nur; Maharani, Ayu (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Dysphagia, or difficulty swallowing, is a common clinical symptom that often reflects structural or functional abnormalities of the upper gastrointestinal (GI) tract. Accurate imaging of the esophagus, stomach, and duodenum (ESD) is essential for identifying the underlying causes. This study aimed to describe radiologic examination techniques for ESD assessment in dysphagia cases at the Radiology Department of Panembahan Senopati Bantul Hospital. A qualitative case study design was applied, involving one radiologist and three radiographers. Data were obtained through direct observation, in-depth interviews, and document analysis, and processed using data reduction, categorization, and open coding, then validated with relevant radiologic literature. Patient preparation included 6–8 hours of fasting, removal of metallic objects, and procedural explanation. Imaging was performed in stages: the stomach was evaluated with AP supine and PA prone projections, the esophagus with AP erect and RPO projections, and the duodenum with an AP full-filling projection. Projection selection was guided by clinical indication, patient comfort, and technical efficiency. For example, AP and RPO projections were sufficient for esophageal evaluation due to its small diameter. The AP supine view was used to assess the corpus ventriculi, while PA prone provided better visualization of the fundus. All examinations were performed under radiologist supervision and adjusted based on patient condition and available equipment. Additional projections were unnecessary if no abnormalities were detected. In conclusion, ESD examination for dysphagia at this hospital follows a systematic yet flexible protocol, ensuring diagnostic accuracy while maintaining patient safety and comfort.